Calibrating and recommissioning the ALICE transition radiation detector - Barrella, Jason (Department of Physics, 2024)
Starting from the year 2022, the LHC produces a factor 6 increase in the interaction rate of Pb-Pb collisions from 8 to 50 kHz, offering exciting new avenues of research in the field of heavy-ion physics. Changes to the ALICE experiment include the introduction of an entirely new software framework as well as an approximate 100 fold increase in statistics and significant improvements in tracking capabilities which will further expand the realm of potential research. The work presented here consists of three primary parts. Firstly, in preparation for new detector control systems at CERN, core software for the ALICE Transition Radiation Detector was updated and migrated to a new version control system. Pipelines were also developed to automatically deploy packages to remote repositories. Secondly, drift velocity and $E times B$ calibration software was developed and tested on Run 2 data. A mean angular resolution of 2.6$^circ$ was achieved. This was found to be within a range of a previous result that could be plausibly explained by a number of factors. Finally, components were written in the new ALICE O$^2$ software framework with applications in calibration, TRD geometry transformations, and a new TRD event display. All were tested successfully and the event display was deployed to the new TRD web page.